2017
DOI: 10.1016/j.rser.2016.11.043
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of Florida's ocean thermal energy conversion (OTEC) resource

Abstract: Technological advances in marine renewable energy allow for various methods of extracting energy in the form of electrical power from the ocean. One method is through the process of ocean thermal energy conversion (OTEC). This study assesses the distributions of electrical power that can be extracted from the ocean around the state of Florida. The OTEC resource is analyzed with the combination of a state-of-the-art ocean circulation model, the Hybrid Coordinate Ocean Model, along with a state-of-the-industry O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 27 publications
(35 reference statements)
2
15
0
1
Order By: Relevance
“…Additionally, for the same temperature change, Uehara and Ikegami showed a decrease of 44% in the net power output of the OTEC power plant [23]. In their paper, VanZwieten et al showed a decrease of 20% and 16% when the temperature changed from 20.12 • C to 21.72 • C and from 20.12 • C to 21.37 • C, respectively, against a 17% drop in this study when a 1.5 • C change occurred [31]. For a change of 5 • C in the seawater source temperature, the calculated drop in w net,max was 45%.…”
Section: Carnot Cycle Resultssupporting
confidence: 47%
See 1 more Smart Citation
“…Additionally, for the same temperature change, Uehara and Ikegami showed a decrease of 44% in the net power output of the OTEC power plant [23]. In their paper, VanZwieten et al showed a decrease of 20% and 16% when the temperature changed from 20.12 • C to 21.72 • C and from 20.12 • C to 21.37 • C, respectively, against a 17% drop in this study when a 1.5 • C change occurred [31]. For a change of 5 • C in the seawater source temperature, the calculated drop in w net,max was 45%.…”
Section: Carnot Cycle Resultssupporting
confidence: 47%
“…For a change of 5 • C in the seawater source temperature, the calculated drop in w net,max was 45%. The difference in the decrease of the net power output with other studies can be explained by the fact that the authors considered water ducting as well as the working fluid circulation pump [17,23,30,31]. Therefore, when the temperature difference decreases, the gross power output greatly decreases, whereas losses due to pumping and pressure drop hardly change.…”
Section: Carnot Cycle Resultsmentioning
confidence: 90%
“…Generally speaking, ocean thermal energy refers to the heat energy arising from the thermal gradients between the surface and deep seawater. It is commonly considered that ocean thermal energy is a viable energy source when thermal gradients exceed approximately 20°C between surface and deep waters . Benefited from the unique geographical conditions, China has a huge ocean thermal energy reserves.…”
Section: Status Quomentioning
confidence: 99%
“…It is commonly considered that ocean thermal energy is a viable energy source when thermal gradients exceed approximately 20°C between surface and deep waters. 23 Benefited from the unique geographical conditions, China has a huge ocean thermal energy reserves. It is estimated that the potential installed capacity of ocean thermal energy stored in China's offshore and adjacent sea areas is about 359.5~373 × 10 3 MW.…”
Section: Marine Renewable Energy Endowmentmentioning
confidence: 99%
“…There is great interest in the development of highly efficient transfer and conversion systems as well as materials to transfer the energy or convert it into other forms of energy such as electricity. 1,2 Phase change materials (PCMs), possessing the ability to absorb and release energy in the process of changing phase, have drawn a lot of attention due to their high latent heat in applications. [3][4][5][6] One important type is the hydrated salt PCM, which has been a study hotspot in the eld of low temperature due to distinct advantages such as high heat fusion, low price, and high security in energy storage systems.…”
Section: Introductionmentioning
confidence: 99%